Brain-eating amoebae : biology and pathogenesis of Naegleria fowleri - Siddiqui, Ruqaiyyah; Ali, Ibne Karim M.; Cope, Jennifer R.; Khan, Naveed Ahmed (Caister Academic Press, 2016)
This concise book on N. fowleri serves as a quick guide for clinical practitioners, health professionals, researchers and students working with this parasite. Divided into easy-to-follow sections, the book covers all aspects of research into N. fowleri as an organism ranging from clinical and laboratory diagnosis to growth and life cycle. It is essential reading for all microbiologists, immunologists, physicians, public health officials and researchers (both new and experienced) involved with N. fowleri. This book is an invaluable reference for everyone working in the field of basic and medica.